A case of abnormal overvoltages in a Petersen grounded 132-kV system caused by broken conductor. - Gustavsen, B.
This paper analyzes a case where a broken phase conductor in a Petersen grounded system caused extensive damage and outages due to excessive stationary overvoltages. It is shown that the high overvoltages resulted from a combination of the following: (1) the fault occurred on a radial connection, (2) the total compensation was close to 100%, and (3) the compensation of the two subnetworks defined by the fault was far from 100% (one subnetwork was undercompensated and the other overcompensated). Overvoltages calculated by a simple model compare favorably with recorded results. The overvoltages are shown to be strongly dependent on the compensation level, the compensation distribution, the shunt conductance to ground, and the load. A least squares method is used for estimating the shunt conductance based on a measured resonance curve.
Keywords: 132 kV; Norway; Petersen coils; Petersen grounded system; Abnormal overvoltages; Arc suppression coils; Broken phase conductor; Compensation distribution; Compensation level; Fault; High overvoltages; Least squares method; Radial connection; Regional transmission systems; Resonance curve; Shunt conductance; Stationary overvoltages; Subnetworks compensation; Total compensation